Pattern of Drug Use in Influenza Self-Medication Efforts in Communities in Bettet Village, Pamekasan Regency: Pola Penggunaan Obat dalam Upaya Swamedikasi Influenza pada Masyarakat di Desa Bettet, Kabupaten Pamekasan - Achmad Fairuz Zabadi; Septiana Kurniasari (Journal Pharmasci (Journal of Pharmacy and Science), 2022)
Influenza is the most common disease in humans. The average person gets influenza twice a year. To treat influenza, people usually take self-medicationby consuming medicines that are freely purchased at pharmacies or drug stores.This research aims to determine the pattern of drug use in an effort to self-medicate influenza in the community in Bettet Village, Pamekasan Regency. This research is descriptive, using questionnaires distributed to 100 respondents who meet the inclusion criteria. The results of this research were 69% of respondents used modern medicine, most of whom consumed MFB (42.03%), while 31% of the population used traditional medicine, of which 41.93% consumed chopped turmeric, ginger and lemongrass.The public believes that modern medicines circulating in Indonesia have guaranteed availability by the government, are safe, quality and useful and are available in sufficient and affordable quantities and types.